تحليل كلام الإنشاء الطلبي ومعانيه في أشعار لبيد بن ربيعة العامري - Akbar, Dhaif (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
An arabic poetry is arabian pride a time of ignorancce. They complete to make poetry as their pride. Labid bin Rabi’ah is a poet who lived in two periods, Jahil and Islamic period. He has many works including diwan Labid bin Rabi’ah, it was the most collection work at the time. The aim of this study is to analyze the form and meaning of kalam insya’ thalabi in Labid bin Rabi’ah’s poetry. This study is used qualitative descriptive method (to describe and explain about this study) and also analytical method (as a tool to examine it more deeply). The result of the study stated that kalam insya’ thalabi in Labid bin Rabi’ah’s poetry is amar (command word) 12 stanzas, nahi (prohibition) 6 stanzas, istifham (question) 24 stanzas, tamanni (hope) 7 stanzas, nida’ (citation) 4 stanzas. As seen of the form side, there are several form of kalam insya’ thalabi which includes amar (command), nahi (prohibition), istifham (question), tamanni (hope), nida’ (citation). As seen of meaning side, it has true meaning original and idhafi. they are ta’jiz (weaken), iltimas (the utterance to people who has the same age), tahdid (threat), irsyad (intruction) and taqrir (affirmation).